2022
DOI: 10.3390/jcm11123486
|View full text |Cite
|
Sign up to set email alerts
|

Expert Multinational Consensus Statement for Total Intravenous Anaesthesia (TIVA) Using the Delphi Method

Abstract: Introduction: The use of total intravenous anaesthesia (TIVA) has been well established as an anaesthetic technique over the last few decades. Significant variation in practice exists however, and volatile agents are still commonly used. This study aims to determine the motivations and barriers for using TIVA over the use of volatile agents by analysing the opinion of several international anaesthetists with specific expertise or interests. Methods and participants: The Delphi method was used to gain the opini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…A recent international consensus statement from 29 panellists found that they would prioritise TIVA over inhalational anaesthesia in paediatric patients to reduce PONV, to improve the effects on physiology, and to increase its availability. Cost and lack of familiarity or training were not considered obstacles to the use of TIVA 6 . In contrast, 144 respondents in our survey chose unfamiliarity as a reason not to use TIVA in obstetric patients.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…A recent international consensus statement from 29 panellists found that they would prioritise TIVA over inhalational anaesthesia in paediatric patients to reduce PONV, to improve the effects on physiology, and to increase its availability. Cost and lack of familiarity or training were not considered obstacles to the use of TIVA 6 . In contrast, 144 respondents in our survey chose unfamiliarity as a reason not to use TIVA in obstetric patients.…”
mentioning
confidence: 74%
“…Cost and lack of familiarity or training were not considered obstacles to the use of TIVA. 6 In contrast, 144 respondents in our survey chose unfamiliarity as a reason not to use TIVA in obstetric patients. Forty-five percent (134/298) of obstetric anaesthetists surveyed did have some experience in using TIVA in the obstetric population, albeit rarely.…”
mentioning
confidence: 92%
“…Paediatric TIVA has gained popularity in the last decade, but there remain barriers, perceived and actual, to its wider adoption. These include: lack of training and experience; unreliable pharmacokinetic models, leading to concerns around awareness or prolonged sedation; lack of availability of essential equipment; concerns about propofol-related infusion syndrome; and the ubiquity of inhalational inductions [44,45]. The environmental benefits of TIVA in the paediatric population have been shown using mathematical modelling and lifecycle analysis to answer several questions around the relative carbon footprints of TIVA and volatile anaesthesia in children of differing weights undergoing procedures of varying durations [46].…”
Section: While Regional Anaesthesia As the Sole Anaestheticmentioning
confidence: 99%
“…Another unusual situation at risk of MH is sedation with inhaled anesthetics in the pediatric intensive care unit (PICU) [ 66 , 67 , 68 ]. If these types of sedation devices are used, children susceptible to MH in the PICU may be at risk for such exposure, highlighting the significance of MH differential diagnosis in intensive care patients admitted for other conditions [ 69 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Moreover, pediatric regional anesthesia is usually performed in combination with general anesthesia or some degree of sedation. There is no evidence to support elective intensive care unit management of MH-susceptible patients after uneventful trigger-free anesthesia [ 67 ].…”
Section: Perioperative Recommendations For High-risk Childrenmentioning
confidence: 99%